El Processoner antic de la catedral de Tortosa (Tortosa, Arx. Cap., ms 267) - Gros i Pujol, Miquel dels Sants (Miscel·lània litúrgica catalana, 2010)
The Ms. Arxiu Capitular de Tortosa 267 contains the most ancient Processional book preserved from this episcopal see. It is dated in the third quarter of the 14th century and it is surprisingly simple considering its advanced datation. However, it contains complete information on the processional rituals in Tortosa. Its gaps have been reconstructed from Ms. Tortosa 266, a little posterior. The texts of this second ms. are included in appendix.